Comparison of the clinical effect of unilateral transverse process extrapedicular and bilateral transpedicular percutaneous kyphoplasty for thoracolumbar osteoporotic vertebral compression fracture - Xu, Dingli; Ruan, Chaoyue; Wang, Yang; Hu, Xudong; Ma, Weihu (Frontiers in Surgery, 2024)
Background Osteoporosis vertebral compression fractures (OVCF) are common with the aging process. This study aimed to compare the effects of unilateral transverse process extrapedicular (UEPKP) and bilateral transpedicular percutaneous kyphoplasty (BTPKP) for patients with thoracolumbar OVCF. Methods Data from 136 patients with OVCF treated with single-level PKP in our hospital between May 2019 and April 2021 were studied. Patients were grouped based on surgical procedure: there were 62 patients in the UEPKP group and 74 in the BTPKP group. All clinical and radiological data were collected from medical records. Clinical outcomes, including visual analog scale (VAS), Oswestry Disability Index (ODI), and Japanese Orthopaedic Association (JOA) scores of the lumbar spine, were evaluated preoperatively, postoperatively, and at the follow-up visit. The radiological evaluations (anterior vertebral height rate and local kyphosis angle) and complications were also collected. Results All patients had successfully improved after surgery. In the UEPKP group, patients showed a significantly shorter operating time and lower fluoroscopy frequency than patients in the BTPKP group (p < 0.05). However, a significantly better distribution score and cement volume were found in the BTPKP group (p < 0.05). The UEPKP group achieved a significantly better VAS score (0.6 ± 0.5 vs. 0.9 ± 0.8) and ODI (24.7 ± 3.1 vs. 27.5 ± 1.8) at the final follow-up visit than the BTPKP group (p < 0.05). The UEPKP group showed significantly worse radiological outcomes (anterior height rate and local kyphosis angle) at the 6- and 12-month follow-ups (p < 0.05). As for complications, the UEPKP group showed significantly fewer facet joint violations and intraspinal leakages (p < 0.05). Conclusion UEPKP could be a safe and effective alternative procedure for patients with thoracolumbar osteoporotic vertebral compression fracture, which possesses an apparent advantage in reducing intraspinal leakage and facet joint violation over BTPKP.